Fungal Infections and Health Literacy: The Media in Community Health Awareness (Türkiye Sağlık Okuryazarlığı Dergisi, 2026)
Fungal infections are increasingly recognized as a pressing public health issue due to their substantial morbidity and mortality, particularly in immunocompromised populations. The emergence of antifungal resistance underscores the need for robust surveillance and effective community-based prevention strategies. Despite this burden, public awareness and understanding of fungal diseases remain limited, reflecting the critical role of health literacy in shaping health behaviors and outcomes. Health literacy (HL) refers to the ability of individuals to access, comprehend, interpret, and apply health-related information; inadequate HL contributes to misconceptions, delayed health-seeking behavior, and poor treatment adherence. Media plays a pivotal role in shaping community perceptions by producing and disseminating health information. The transition from traditional to digital and social media has expanded access to diverse health messages, but it has also increased the risk of misinformation. Media literacy is therefore essential to empower individuals and communities to critically assess health messages and to make informed health decisions. This review explores the epidemiology of fungal infections, the influence of health literacy on diagnostic and treatment pathways, and the media’s role in constructing public perceptions. It emphasizes the integration of health and media literacy as a strategy to improve community health outcomes. Drawing on national and international examples, the paper highlights the impact of media on public health and provides recommendations for strengthening accurate information dissemination and health education within communities.